RESEARCHING OF HOUSEHOLD ELECTRICITY CONSUMPTION IN THE CITY OF KARAKOL (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In order to improve the quality of decisions made in the tariff policy and ensure the quality of electricity, it is of particular importance to clearly define the consolidated structure of subscribers and their distribution by electricity consumption ranges. On the basis of probabilistic and statistical calculations in Karakol, the law of distribution of household electricity consumption is determined.
Keywords: electricity consumption, statistics, choice, living space, private sector, histogram.